2003
DOI: 10.1074/jbc.m212697200
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surfactant Protein-A (SP-A) Restores the Surface Properties of Surfactant after Oxidation by a Mechanism That Requires the Cys6 Interchain Disulfide Bond and the Phospholipid Binding Domain

Abstract: Reactive oxygen species produced by activated leukocytes in the alveolar epithelial lining fluid have been implicated in the inactivation of pulmonary surfactant and the impairment of lung function. Oxidation of bovine lipid extract surfactant (BLES), a therapeutic surfactant, with hypochlorous acid (H-BLES) or the Fenton reaction (F-BLES) led to temporary increases in conjugated dienes and formation of malondialdehyde and 4-hydroxy-2-nonenal. Electrospray ionization mass spectrometry revealed the appearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…The primary source of phospholipids (PLs) in the lung is pulmonary surfactant, synthesized and released by alveolar epithelial type II cells. The surfactant contains approximately 80-90% PLs, with fatty acid chains that can be oxidized during different challenges in the lung [85]. The oxidation of these PLs in the lung can occur in the setting of an increased oxidative stress situation, such as infection and inflammation [86].…”
Section: Discussionmentioning
confidence: 99%
“…The primary source of phospholipids (PLs) in the lung is pulmonary surfactant, synthesized and released by alveolar epithelial type II cells. The surfactant contains approximately 80-90% PLs, with fatty acid chains that can be oxidized during different challenges in the lung [85]. The oxidation of these PLs in the lung can occur in the setting of an increased oxidative stress situation, such as infection and inflammation [86].…”
Section: Discussionmentioning
confidence: 99%
“…This is clearly not the case. Presence of protein SP-A has been also proposed as protective of surfactant inhibition, again as a consequence of the protein promoting the assembly of more compact and complex lipid/protein membrane networks [ 46 48 ]. Our results seem to indicate that these differences in membrane complexity potentially promoted by SP-A are not associated with reduced cholesterol incorporation but with transfer of larger amounts of sterol and higher susceptibility to functional inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the conserved nature of both SP-B and SP-C in mammalian lungs, and their tight association with the surfactant lipids, it is clear that both play a role in surfactant function. A combined role for both proteins is supported by numerous reconstitution and synthetic pulmonary surfactant preparation studies, demonstrating that superior in vitro activities occur with the combined proteins. ,, Similarly, optimal physiological responses to exogenous surfactant in premature rabbits require the presence of both proteins. ,, It has been suggested that the fusogenic properties of SP-B both compliment and counteract the membrane destabilizing effects of SP-C, observed with small vesicles. , A notable indication of the cooperative roles of these two proteins is that including physiological amounts of cholesterol inhibits the ability of surfactant-like mixtures (DPPC:POPC:POPG) containing SP-B to attain low γ during compression. Mixtures containing SP-C alone have very high γ max values.…”
Section: How Does Pulmonary Surfactant Adsorb Rapidly?mentioning
confidence: 99%
“…Lysophospholipid generated via phospholipase A2 activity not only inhibits surfactant function, but it also makes surfactant more susceptible to inhibition by serum proteins. Finally, exposing exogenous surfactant to reactive oxygen species leads to less γ reduction, mainly due to oxidative modifications, and consequently impaired function, of SP-B and SP-C, although the PL are also affected. ,,, …”
Section: How Does Pulmonary Surfactant Reduce Surface Tension To Low ...mentioning
confidence: 99%
See 1 more Smart Citation